PENGARUH PENGELOLAAN FAKTOR INTERNAL USAHATANI TERHADAP PRODUKSI KOPI DI PROVINSI LAMPUNG - Robet Asnawi; Ratna Wilis Arief (Jurnal WACANA PERTANIAN, 2020)
Coffee is a leading export commodity in Lampung Province. The main problem in coffee farming is low productivity and low farmers income. Coffee plant productivity has tended to decline in the last 3 years. Coffee productivity in West Lampung Regency was recorded at 1.205 kg/ha in 2016, down to 961 kg/ha in 2018, and coffee productivity in Tanggamus Regency in 580 kg/ha in 2016 down to 457 kg/ha in 2018. The use of organic fertilizer relatively low at 33,3% in West Lampung Regency and 30,2% in Tanggamus Regency. Polatanam which is commonly done by coffee farmers in Lampung Province is mixed cropping of 84.12% and coffee monoculture only 15,88%. Factors that influence of coffee production in Lampung were land area, the use of organic fertilizer, the use of top-grafted seedlings, farmers income, and age of coffee plants.